The Development of Professionals for Research Management in Malaysia - Tan, Hsiao Wei (Journal of Research Management and Governance, 2020)
Research activities in Malaysian universities have increased dramatically since the year 2007. Since then, the role of the research management office has evolved due to the increasing demand internally and externally. Traditionally, academics are seconded to manage research at local universities. In view of the growing complexity and volume of tasks and responsibilities in managing research, the development of the research management profession is critically needed. However, the profession was only the initiative of individual universities and wasn’t formally recognised at the national level. The turning point of this situation happened in 2015, where there was support from the Ministry when a two-phase project related to the enhancement of research management was initiated at the national level. The project studied the strengths and weaknesses of current research management practices in Malaysian public universities and the drafting of strategies and action plans for implementation. One of the recommendations from the Malaysian Research Management & Governance Project (MRMG) project was to develop a network for research managers and administrators in Malaysia so that this group of professionals can improve and learn from their peers via the sharing of best practices and exchange ideas. The first association of the profession was established in 2019 after three hardworking years since the Phase I concluded. The establishment of the association indicated that the acceptability of the profession into the academic communities and universities.